To love or to eat the super-pig: Bong Joon-Ho’s Okja (2017)—an ecocritical and transnational perspective - Ang, Bin Yee (Frontiers in Communication, 2025)
This article analyses Bong Joon-ho’s Okja, a co-production between South Korea and the United States, from the perspective of ecocriticism and its transnational nature within the context of film studies and animal ethics. Bong uses a compelling narrative about the relationship between a rural teenage girl, Mija, and her porcine companion, the genetically modified (GM) super-pig, Okja, to prompt a critical reflection on the ethical implications of meat consumption and capitalism. It sparks the dilemma of whether to eat or love the creature. The significance of Bong’s Okja in the discourse surrounding human-animal relationships stems from a dialectical perspective—it simultaneously critiques human exceptionalism within a capitalist framework whilst also embracing the technological depiction of livestock and the advantage of global distribution facilitated by the giant streaming platform, Netflix. This article does not advocate an absolute resolution to human-animal reconciliation; rather, it offers an ecocriticism and perspective on film culture in relation to animal ethics. It explores the film from a seemingly biophilic and de-centring anthropocentric point of view. The question of animals transcends geographical and cultural boundaries.